Anak menjadi wali nikah ibu perspektif hukum islam - mutmainnah, siti (AS-SAKINAH, 2023)
The case in Sumberpoh Village, Maron Sub-district, Probolinggo Regency, there was a siri marriage between a widow and a widower. The researcher has conducted a pre-survey in Sumberpoh by interviewing Mrs. Tun as a relative who was present at the marriage contract between Mrs. S and Mr. I. Where the marriage between Mrs. S and Mr. I who acts as a marriage guardian is not included in the order of guardians in accordance with what is listed in KHI, but the one who acts as a marriage guardian is the son of Mrs. S with the initials F, because indeed Mrs. S is a widow with 1 child. The author uses the type of field research. This research was conducted in Sumberpoh Village, Maron District, Probolinggo. The majority of scholars are of the opinion that women cannot marry themselves or marry others. Shafi'i, Maliki, and Hambali are of the opinion that if a woman who has reached puberty and has the right to marry herself is still a girl, then it is the guardian who has the right to marry her. But if she is a widow, then the right lies with both of them. So for the status of a widow she has more rights over herself, meaning that a widow when getting married is allowed without a guardian.